Overlooked effects of wavefront reception with or without speed limit, from aberration to time measurement - Denis Michel (Results in Optics)
A general approach to wavefront reception applicable to any type of wave allows to point out some overlooked aspects and ignored consequences of established theories. The Doppler and aberration effects of electromagnetic waves, the cosmological redshift and the measurement of durations are all perceptual phenomena, and as such require the use of reception rather than Lorentz-transformed coordinates, since perceived durations relate proper to proper durations whereas the famous time dilation of special relativity relates proper to improper durations. Taking this subtlety into account rehabilitates the controversial Poincaré ellipsoid whose polar equation is just the relativistic Doppler effect. The application of this approach to the Galilean case whose transformed and received wavefronts are homothetic, reveals new aberration relations and the existence of a transverse Doppler effect very similar, in proportion to the respective wave velocities, to the relativistic one, thus forbidding in practice the test of his theory proposed by Einstein. The reasons for the long persistence of a classical angular Doppler formula divorced from wavefront reception are discussed, one of them ironically being the theory of special relativity.